Cervical Sagittal Alignment: Literature Review and Future Directions - Lee, Sang Hun; Hyun, Seung-Jae; Jain, Amit (Neurospine, 2020)
Cervical alignment as a concept has come to the forefront for spine deformity research in the last decade. Studies on cervical sagittal alignment started from normative data, and expanded into correlation with global sagittal balance, prognosis of various conditions, outcomes of surgery, definition and classification of cervical deformity, and prediction of targets for ideal cervical reconstruction. Despite the recent robust research efforts, the definition of normal cervical sagittal alignment and cervical spine deformity continues to elude us. Further, many studies continue to view cervical alignment as a continuation of thoracolumbar deformity and do not take into account biomechanical features unique to the cervical spine that may influence cervical alignment, such as the importance of musculature connecting cranium-cervical-thoracic spine and upper extremities. In this article, we aim to summarize the relevant literature on cervical sagittal alignment, discuss key results, and list potential future direction for research using the '5W1H' framework; "WHO" are related?, "WHY" important?, "WHAT" to evaluate and "WHAT" is normal?, "HOW" to evaluate?, "WHEN" to apply sagittal balance?, and "WHERE" to go in the future?Cervical alignment as a concept has come to the forefront for spine deformity research in the last decade. Studies on cervical sagittal alignment started from normative data, and expanded into correlation with global sagittal balance, prognosis of various conditions, outcomes of surgery, definition and classification of cervical deformity, and prediction of targets for ideal cervical reconstruction. Despite the recent robust research efforts, the definition of normal cervical sagittal alignment and cervical spine deformity continues to elude us. Further, many studies continue to view cervical alignment as a continuation of thoracolumbar deformity and do not take into account biomechanical features unique to the cervical spine that may influence cervical alignment, such as the importance of musculature connecting cranium-cervical-thoracic spine and upper extremities. In this article, we aim to summarize the relevant literature on cervical sagittal alignment, discuss key results, and list potential future direction for research using the '5W1H' framework; "WHO" are related?, "WHY" important?, "WHAT" to evaluate and "WHAT" is normal?, "HOW" to evaluate?, "WHEN" to apply sagittal balance?, and "WHERE" to go in the future?